The influence of the effectiveness of public transport on the well-being mobility of the population: A literature review - Rima , Abdul Rahman; Harifah , Mohd Noor; Imang, Ubong; Eboy, Oliver Valentine (GEOGRAFI, 2024)
Mobility well-being refers to an individual’s ability to travel freely and safely in an unobstructed environment. Effective and inclusive mobility plays an important role in improving the well-being of the population to access basic social facilities easily and effectively. Therefore, efficient and effective public transport is important in improving the well-being of human mobility. This study is to discuss how the effectiveness of public transport can affect the well-being of user mobility. This study uses a database from the internet, namely 6 articles from Scopus, 15 articles from science direct, and 17 articles from google scholar to select articles by including keywords such as ’mobility well-being’ and ’public transport effectiveness’. Thematic analysis is used in this study to classify the factors of public transport effectiveness that affect the well-being of users’ mobility. The findings show that there are three main factors in measuring the effectiveness of public transport, namely accessibility, reliability, and safety. The effectiveness of public transport affects the well-being of population mobility from the aspect of easy access to public facilities, reducing air pollution that adversely affects individual travel, reducing road congestion, and providing psychological health while traveling. Therefore, by improving the effectiveness of public transport, residents can achieve a happier journey. This study has implications for local authorities, urban planners, and infrastructure developers in formulating more productive policies aimed at enhancing public transportation effectiveness.